2016
DOI: 10.1177/0954406216645129
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational analysis of single-layered silicon carbide nanosheets and single-walled silicon carbide nanotubes using nanoscale finite element method

Abstract: A three-dimensional finite element model has been used here to study the vibrational behavior of silicon carbide nanosheets and nanotubes. The bonds of hexagonal lattices of SiC nanosheets have been modeled by structural beam elements, and at the corners, mass elements are placed instead of Si and C atoms. Moreover, molecular dynamics simulations are performed to verify the finite element model. Comparing the results of finite element model and molecular dynamics simulations, it is concluded that the utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The studies reported so far on the dynamic properties of N-CNTs mainly addressed the theoretical analysis of the vibrational behaviour of BNNTs [34,48,57,63,[67][68][69][70][71]98,99] and SiCNTs [100,101].…”
Section: Vibtational Properties Of N-cntsmentioning
confidence: 99%
“…The studies reported so far on the dynamic properties of N-CNTs mainly addressed the theoretical analysis of the vibrational behaviour of BNNTs [34,48,57,63,[67][68][69][70][71]98,99] and SiCNTs [100,101].…”
Section: Vibtational Properties Of N-cntsmentioning
confidence: 99%
“…However, SiC possesses high hardness and chemical inertness which bring many challenges to the manufacture of abrasive-based nano-surface. 9,10 Abrasive machining is one of the most important processes used in manufacturing engineering. 11 Some experimental researches have been conducted in the field of chemical mechanical polishing processes for obtaining ultra-smooth SiC surface.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The wide band gap, high limit operating temperature and thermal conductivity, high breakdown electric field strength, excellent oxidation and neutron irradiation resistance, corrosion and wear resistance, which makes SiC becoming promising material in harsh environment. [7][8][9][10] The thermal expansion coefficient and lattice constant of single-crystal SiC are similar to those of gallium nitride (GaN), which effectively solves the problem of low lattice matching between substrate materials and gallium nitride.…”
Section: Introductionmentioning
confidence: 99%